Octobre des Arts - Lyon 1984. (Lyon : Musée St. Pierre Art Contemporain, 1984)
Collection 1984: Aballéa, Martine ; Anselmo, Giovanni ; Barry, Robert ; Beaugrand, Catherine ; Boezem, Marinus ; Boltanski, Christian ; Byars, James Lee ; Chopy, Marc ; Riverhead (New York) ; Fontana, Lucio ; Gavoty, Jean-François ; Raynaud, Patrick ; Schütte, Thomas ; Sonnier, Keith ; Braconnier, Stéphane ; Dauvergne, Michel ; Gilbert & George ; Lecoffre, Gilles ; Merz, Mario ; Noua, Kacem ; Pouillet, Alain ; Reigl, Judit ; Schütte, Thomas ; Aubanel, Jean-Philippe ; Becher, Bernd & Hilla ; Bertholin ; Blacker, Kate ; Blocher, Sylvie ; Bouillon, François ; Burgin, Victor ; Burkhard, Balthasar ; Buthe, Michael ; Cragg, Tony (Anthony) ; Defraoui, Silvie & Cherif ; Fulton, Hamish ; Gerz, Jochen ; Gette, Paul-Armand ; Giorda, Patrice ; Gudmundsson, Sigurdur ; Guillaumon, Jean-Claude ; Gac, Jean Le ; Hilliard, John ; Leisgen, Barbara & Michael ; Lüthi, Urs ; Mach, David ; Messager, Annette ; Palestine, Charlemagne ; Perrin, Carmen ; Poivret, Jean-Luc ; Saytour, Patrick ; Scanreigh, Jean Marc ; Ughetto, Henry ; Vilmouth, Jean-Luc ; Woodrow, Bill ; Zagari, Carmelo ; Collin-Thiébaut, Gérard ; Krauth, Jean-Marie
Deel L: Octobre des Arts : Josef Félix Müller, 26 p. ; zw/w ill., kl. ill. ; 31 x30,5 cm (Frans & Duits)
Octobre des Arts - Lyon 1984, Musée St. Pierre Art Contemporain, Lyon, 1984
biografie
Frans & Duits & Engels
kunstcatalogus
Keywords: Lafontaine, Marie-Jo; Baselitz, Georg; Nils-Udo; Zimmer, Bernd; Allen, Terry; Ughetto; Adilon, Georges; Paladino, Mimmo; Kirili, Alain; Müller, Josef Felix